AB0601 RAPID AND SUSTAINED EFFICACY OF AN INDUCTION TREATMENT WITH A TRIPLE THERAPY INCLUDING HIGH-DOSE INTRAVENOUS IMMUNOGLOBULINS, METHOTREXATE AND GLUCOCORTICOIDS IN ANTI-3-HYDROXY-3-METHYLGLUTARYL-COENZYME A REDUCTASE MYOPATHY. (2nd June 2020) - Treppo, E.; Infantino, M.; Benucci, M.; Ravagnani, V.; Palterer, B.; Grandis, M.; Fabris, M.; Tomietto, P.; Manfredi, M.; Sonaglia, A.; Giudizi, M. G.; Ligobbi, F.; et al.
Abstract : Background: Anti-3-hydroxy-3-methylglutaryl-coenzime A reductase (HMGCR) myopathy is a new entity, which has been clearly associated to statin use, even if it can be diagnosed in patients without a history of exposure to statin or even in the childhood (1). Objectives: The aim of the study is to describe the efficacy of a triple therapy regimen consisting in high-doses of intravenous immunoglobulins (IVIG), methotrexate (MTX), and glucocorticoids (GC) in 16 patients with Anti-HMGCR myopathy enrolled in 6 specialized centres. Methods: A total of 16 patients with anti-HMGCR myopathy (7 females; 9 males) were collected. Mean (±standard deviation) age at the onset of disease was 72.4±10.3 years old. All patients were diagnosed having anti-HMGCR myopathy [anti-HMGCR antibodies were measured by chemiluminescence assay (BioFlash, Inova, CA)] (2). Median follow-up was 29.5 months (interquartile range: 15.75-60 months). Anti-HMGCR antibodies were available in the follow-up in 8/16 patients. Results: Thirteen out of 16 patients (81.3%) had been exposed to statin (1/13 to red rice), 3/16 (18.7%) were not exposed. As induction therapy, 11/16 patients have been treated with triple therapy (high-dose IVIG, MTX and GC), 2/16 with double therapy (high-dose IVIG and GC), 2/16 have been treated with GC alone, the patient exposed to red rice resolved only with red rice suspension. Clinical remission and normalization of CPK values within month +24 were obtained in all the patients. All the patients were in remission at the last follow-up. Gradual improvement started soon from the first month, and among the 13 patients treated with an aggressive immunosuppresssive therapy including IVIG (13/13), GC (13/13) and methotrexate (11/13), 9/13 normalized the CPK value within 6 months. Clinical and laboratory response was accompanied by significant decrease or normalization of the anti-HMGCR antibody titer. All the patients were either not taking GC (56.3%), or were taking low doses of GC (43.7%) at the last follow-up. Four patients had stopped GC within 6 months. No serious side effects were recorded. After persistent remission, a maintenance immunosuppressive therapy was then administered. Only 3 relapses in 3 different cases were recorded, all of them during drug-free remission in long-term follow-up. Reinduction was again effective in all. Conclusion: Anti-HMGCR myopathy is a rare and serious myopathy which usually affects older people during statin treatment. After statin suspension, a rapid and sustained remission can be achieved by induction with a triple aggressive therapy consisting in medium-to high doses of GC, high-dose IVIG, and MTX (3). GC should be tapered as soon as possible. Relapse appears infrequent during maintenance treatment. Monitoring anti-HMGCR antibody titer may be clinically relevant. References: [1]AL Mammen et al. N Engl J Med. 2016;374:664-9 [2]Musset L et al. Autoimmun Rev. 2016;15:983-93. [3]Aggarwal A et al. Scand J Rheumatol. 2019; 1-7. Acknowledgments: We thank MD Francesca Grosso and MD Valentina Mecheri from the University of Florence, MD Angela Zuppa and MD Chiara De Michelis, from San Martino Hospital, Genova, for their valued collaboration in data collection Disclosure of Interests: Elena Treppo: None declared, Maria Infantino: None declared, Maurizio Benucci: None declared, Viviana Ravagnani: None declared, Boaz Palterer: None declared, Marina Grandis: None declared, Martina Fabris: None declared, Paola Tomietto: None declared, Mariangela Manfredi: None declared, Arianna Sonaglia: None declared, Maria Grazia Giudizi: None declared, Francesca Ligobbi: None declared, Daniele Cammelli: None declared, Paola Parronchi: None declared, Salvatore De Vita Consultant of: Roche, GSK, Speakers bureau: Roche, GSK, Novartis, Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer